2019
DOI: 10.3390/en12234450
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Operation of Battery Storage for a Subscribed Capacity-Based Power Tariff Prosumer—A Norwegian Case Study

Abstract: The cost of peak power for end-users subject to a demand charge may be substantial, expecting to increase further with the vast growth of power-demanding devices. In cases where load-shifting is not a viable option for cost reduction, battery storage systems used for peak shaving purposes are emerging as a promising solution. In this paper, the economic benefits of implementing battery storage into an existing grid-connected photovoltaic system for a medium-scale swimming facility is studied. The objective is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…For instance, authors in [15] determined the techno-economic feasibility of incorporating distributed energy sources (DER), such as a PV system, and ESSs into a virtual power plant. In this context, F. Berglund et al presented a grid-connected PV system for a medium-scale swimming facility [2]. Authors demonstrated that the installation of a BESS into the existing microgrid is economically beneficial with net savings on the total cost of the system by optimal sizing and controlling of the BESS.…”
Section: State Of the Artmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, authors in [15] determined the techno-economic feasibility of incorporating distributed energy sources (DER), such as a PV system, and ESSs into a virtual power plant. In this context, F. Berglund et al presented a grid-connected PV system for a medium-scale swimming facility [2]. Authors demonstrated that the installation of a BESS into the existing microgrid is economically beneficial with net savings on the total cost of the system by optimal sizing and controlling of the BESS.…”
Section: State Of the Artmentioning
confidence: 99%
“…Similarly, the work presented by Y. Hong et al determines the optimal capacities of energy storage in an islanded microgrid while excluding the optimization of the size of the PV system and energy exchange between the grid and prosumer [22]. A genetic algorithm to optimize the charging and discharging scheduling of prosumer batteries by minimizing the amount of energy exchanged with the main grid was presented by F. Berglund et al [2]. Moreover, several works present various approaches to optimize the energy scheduling of BESS in microgrid applications [23][24][25][26].…”
Section: State Of the Artmentioning
confidence: 99%
See 1 more Smart Citation
“…The operation cost of the battery banks is similar as the cost of life of the renewable energy generation equipment (C bl ) [8,15,[35][36][37][38][39][40]. This is presented in Equation (18), where L loss is the battery life loss and C init-bat is the initial investment cost [8].…”
Section: Operation Cost Of the Battery Banks (F 3 (X))mentioning
confidence: 99%
“…Degradation evolution is very important for the economic analysis of these systems, which are still costly, as already indicated, and whose profitability is still under discussion [18]. In fact, degradation is already a key parameter in the profitability analyses of batteries being proposed in applications, such as ramp rate control of large renewable power generation plants [19,20], ancillary services [21,22], energy arbitrage, and peak shaving provided by large energy storage systems [23,24], and even for electric vehicle integration [25]. Among those published for the residential solar storage sector, some can be highlighted.…”
Section: Introductionmentioning
confidence: 99%